Combination of preoperative tumour markers and lymphovascular invasion with TNM staging as a cost and labour efficient subtyping of colorectal cancer - Tomoki Yamano (Nature Portfolio, 2020)
Abstract Tumour-Node-Metastasis (TNM) staging of colorectal cancer (CRC) needs further classification for better treatment because of disease heterogeneity. Although molecular classifications which are expensive and laborious are under study, cost and labour efficient subtyping is desirable. We assessed the combinations of preoperative tumour marker (TM) elevation and tumour lymphovascular invasion (LVI) as a solution. We used the pooled data of 7151 colon cancer (CC) patients and 4620 rectal cancer (RC) patients who received curative surgery between 2004 and 2008 in Japan. The best-matched subtyping for predicting relapse-free survival (RFS) was statistically selected using the c-index and Akaike’s information criterion. This subtyping (TM-LVI), which consisted of three categories by TM elevation status and severity of LVI status, was an independent prognostic factor for RFS of CC (stage IIa, IIIb, and IIIc) and RC (stage I, IIa, IIb, IIIa, and IIIb) and also for disease specific survival of CC (stage IIa, IIb, IIIb, and IIIc) and RC (all stage except for IIc). Although TM-LVI classified CRC patients into low and high recurrence risk groups, the application of adjuvant therapy was not accordance with the TM-LVI status. TM-LVI may be a cost and labour efficient subtyping of colorectal cancer for better treatment strategy.